The life of Edward Irving forerunner of the Charismatic Movement - Dallimore, Arnold (Edinburgh, Scotland The Banner of Truth, 1983)
Includes bibliographical references and index.
Keywords: Irving, Edward, -- 1792-1834; Charismatic movement -- biography